2000
DOI: 10.1246/cl.2000.1056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pKa of Polymer Microcarriers on Growth of Mouse L Cell

Abstract: In order to obtain fundamental information about the electrostatic effect of microcarriers on fibroblastic cell growth, the aminated poly(γ-methyl l-glutamate) and the cross-linked poly(ε-lysine) beads were prepared. When the growth of mouse L cell on the various beads were determined by common cell culture methods, it strongly depends on the apparent pKa of the beads but not on their amino-group content. The polymer beads with neutral apparent pKa (7.4–7.6), just as in the physiological environment, were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Besides the charge density and the nature of positively charged groups, Masashi Kunitake presented another view that pKa of microcarriers had a great impact on cell growth (Sakata et al, 2000). They cultivated mouse L-929 cells on animated poly(γ-methyll-glutamate) (PG) and cross-linked poly(ε-lysine) (PL) particles containing variable amounts of primary amino groups.…”
Section: Effect Of Surface Charge and Charge Density Of Microcarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the charge density and the nature of positively charged groups, Masashi Kunitake presented another view that pKa of microcarriers had a great impact on cell growth (Sakata et al, 2000). They cultivated mouse L-929 cells on animated poly(γ-methyll-glutamate) (PG) and cross-linked poly(ε-lysine) (PL) particles containing variable amounts of primary amino groups.…”
Section: Effect Of Surface Charge and Charge Density Of Microcarriersmentioning
confidence: 99%
“…The experimental results showed that butyl-and hexyldiamine modified particles provided the most optimal environment. Kunitake modified PG-based [poly(γ-methyl ι-glutamate)] particles with three n-alkyl terminal groups and compared cell growth on the alkylated PG particles with unmodified PG and hydroxyl terminated PG particles (Sakata et al, 2000). They found that cells grew better on the particles modified with longer alkyl chains.…”
Section: Effect Of Hydrophobicity (Wettability) Of Microcarriersmentioning
confidence: 99%
“…Bioactive glass beads, bioceramic hollow microspheres, and biodegradable‐bioactive glass–polymer composite microspheres were comparatively investigated in 3‐D cell culture of osteoblasts 15. Agar‐based beads, poly(γ‐methyl‐ L‐ glutamate) beads, and gelatin–polystyrene magnetic beads were used as microcarriers in mammalian cell culture 16–18. Calcium alginate gel beads crosslinked with gelatin were also tried as a new microcarrier for anchorage‐dependent mammalian cell culture 19.…”
Section: Introductionmentioning
confidence: 99%